LA POLITIQUE PENALE DE LUTTE CONTRE LA DELINQUENCE JUVENILE DANS LA VILLE KISANGANI - Jean Pierre, LITEMA YENI (IJRDO - Journal of Social Science and Humanities Research, 2021)
The city of Kisangani, in the province of Tshopo in the Democratic Republic of Congo, which once was a place of peace and tranquility, a city called "hope" where it was beautiful to live, has now become the place where the tranquillity of its population is disturbed almost every day by the actions of juvenile delinquency. The latter plunges the Boyomais and Boyomais into an upsurge in urban insecurity. This phenomenon, orchestrated by groups of young people in all six communes in particular (Makiso, Kabondo, Kisangani, Lubunga, Mangobo and Tshopo) is a time bomb for the population of the city of Kisangani because, these young people structured in organized groups, tend to escape state authority. So by carrying out this study, it comes down to elucidating the motivations for the rise in power of this juvenile delinquency and analyzing the penal policy to fight against this scourge which is growing day by day and in multiple forms within youth and endangering social peace and the tranquility of the population of the city of Kisangani.